Redesain Fasilitas Pendidikan sebagai Urban Catalyst di Kawasan Peri-Urban Studi Kasus SDN Cinere 1 - Candra Kusuma Rahmat; Narintha Nayla Pritadjaya; Anggi Maharani (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
The rapid development of peri-urban areas driven by urbanization often leads to spatial fragmentation and weakened connectivity among urban functions. This condition is evident in Cinere, Depok, where intensive residential and commercial growth has occurred without adequate spatial integration. This study aims to identify the potential of SDN Cinere 1 as a catalytic node and formulate an urban catalyst-based redesign strategy to strengthen the relationship between educational facilities, public spaces, and commercial activities at the neighborhood scale. The research employed a qualitative approach using a case study method. Data were collected through field observations, Focus Group Discussions (FGDs), literature review, digital maps, satellite imagery, and planning documents. The analysis was conducted by examining the study area, activity patterns, and movement systems, which were subsequently synthesized using the urban catalyst concept. The findings indicate that SDN Cinere 1 possesses the characteristics of a catalytic node, as it generates activities, attracts movement, influences supporting activities in the surrounding area, and connects various urban functions. Based on these findings, a redesign strategy was formulated, including the transformation of the school interface, the development of transitional and communal spaces, and the improvement of the commercial corridor. These findings demonstrate that educational facilities have significant potential to function as catalytic elements in the development of peri-urban areas.